The elements of power lessons on leadership and influence - Bacon, Terry R. (IG library, 2011)
What do a person's knowledge, expressiveness, history, character, and attraction have in common? Or his or her role, resources, information, network, and reputation? Each is a key to either personal or organizational power, and together they open the complex combination lock on the door of true leadership and irresistible influence. The Elements of Power combines the latest research on the nature of power all over the world with a handy self-assessment and invaluable insight into: How power works in organizations How people use and lose power The relationship between power and leadership What makes famous people powerful or what diminishes their power Sources of power and how to build each one Leading and influencing others more effectively Complete with "Portraits in Power" examining key business figures and world leaders alike, the full effect is an accessible and unprecedented pipeline to the many sources and types of internal and external power, including the most valuable of all: the power of will.